Pengembangan Media Video Pembelajaran PAI Meggunakan ‎Plotagon Studio di SMA Islam Nurul Ihsan ‎Palangkaraya - Ulfa Maghfirah; Maliana Julia Saputri; Ilmika Raudhatul Jannah; Eko Giono; Abdul Aziz (Lembag, 2024)
Learning media needs to be developed by utilizing technology supported by the availability of facilities in schools so that students are interested in paying attention to the material being explained with a media. The purpose of this research is to develop video learning media using Plotagon Studio that is feasible and practical for Islamic education learning in the classroom. The research method used is Research and Development (R&D) with the 4D model. The research was carried out at Nurul ‎Ihsan Islamic High School, Palangkaraya. The video learning media in Islamic education was adjusted appropriately through validity and practicality tests. Validation was carried out by media experts and material experts. The results of the validity test of video learning media in Islamic education using Plotagon Studio at Nurul Ihsan Islamic High School Palangkaraya were declared valid with a validation percentage of media experts of 83.75%, and material experts of 76.39%. While the results of the practicality test at the research school were 82.37% for student responses. Thus, the use of video learning media in Islamic education using Plotagon Studio at Nurul Ihsan Islamic High School in Palangkaraya is valid and practical for use in the learning process. ‎